1997
DOI: 10.1002/art.1790100606
|View full text |Cite
|
Sign up to set email alerts
|

Measures of activity and damage in rheumatoid arthritis: Depiction of changes and prediction of mortality over five years

Abstract: Objective. To analyze various quantitative measures of inflammatory activity and joint damage, including articular, radiographic, laboratory questionnaire, and physical function measures, in regard to changes in status in surviving patients and prediction of mortality in non-survivors over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 68 publications
4
67
1
4
Order By: Relevance
“…Typically, disability in RA diminishes within the first year after diagnosis and start of intervention, and then either remains stable but still affected (11) or slowly worsens over time (2,12). Two recent Swedish studies on early RA have found that women on average have more pronounced difficulties in performing daily activities than men as reflected by the HAQ (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, disability in RA diminishes within the first year after diagnosis and start of intervention, and then either remains stable but still affected (11) or slowly worsens over time (2,12). Two recent Swedish studies on early RA have found that women on average have more pronounced difficulties in performing daily activities than men as reflected by the HAQ (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of many early arthritis clinics (and thus, the expanded possibilities for early referral) is a likely explanation for the observation that patients present with less-active disease at the first visit. Callahan et al (22) observed that scores on a modified Health Assessment Questionnaire (M-HAQ) were unchanged over 5 years in a cohort of 100 patients from Tennessee who were monitored from [1985][1986][1987][1988][1989][1990]. This finding contrasted with those of all previous studies, which had documented significant declines in function over 5-15 years.…”
Section: Improved Morbidity In Ramentioning
confidence: 89%
“…For example, mortality over 5 years was analyzed in a series of 210 patients with RA in whom careful quantitative measurements were made at baseline in 1985 (4,22). As might be expected, poorer status at baseline (as indicated by joint counts and radiographic, laboratory, questionnaire, physical function, and demographic measures) predicted decreased survival over the next 5 years.…”
Section: Markers Of Premature Mortality In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatoid arthritis (RA) prognosis is dominated by functional impairment related to joint pain, synovial inflammation, and structural damage (1,2), and by increased cardiovascular morbidity and mortality (3,4). During the past decades, modern conventional and biologic disease-modifying antirheumatic drugs (DMARDs) have been effective to various extents in controlling RA-related inflammation, preventing disease flare, the progression of structural damage (5)(6)(7)(8)(9), and thus overall improvement in RA prognosis (10).…”
Section: Introductionmentioning
confidence: 99%